Comparison of Breastfeeding Support Perceptions Between Postpartum Mothers and Health Care Personnel in Public Hospital - Kartikasari, Aprilia; Latifah, Lutfatul; Susmarini, Dian (Jurnal Keperawatan Soedirman, 2020)
Breastfeeding support can increase postpartum maternal confidence when breastfeeding so that it will indirectly increase the success of exclusive breastfeeding. But there are still many postpartum mothers who still do not get good support due to differences in perceptions between mothers, families and health workers. This study uses a descriptive analytic study method that compares the perception of breastfeeding support perceptions in postpartum mothers and health workers in hospitals. 197 postpartum mothers and 37 health workers in the postpartum room of the hospital in the Purwokerto region filled out a questionnaire containing questions related to breastfeeding support. Sampling for postpartum maternal respondents was carried out by consecutive sampling method, whereas for health workers respondents used total sampling. The results of this study indicate there is a gap in perception between postpartum mothers and health workers related to breastfeeding support for postpartum mothers in several indicators of breastfeeding support, namely teaching how to position and attach correctly, act IMD, provide information on signs your baby is getting enough milk, breastfeeding assistance in hospital, information about cadre and lactation counseling, and information to overcome breastfeeding problems at home. Conclusion: There is still a gap in perception of breastfeeding support between health workers and postpartum mothers during hospitalization.